2018
DOI: 10.1155/2018/1598178
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Cortical and Subcortical Activities during Observation and Motor Imagery of Dynamic Postural Tasks: An fMRI Study

Abstract: Age-related changes in brain activation other than in the primary motor cortex are not well known with respect to dynamic balance control. Therefore, the current study aimed to explore age-related differences in the control of static and dynamic postural tasks using fMRI during mental simulation of balance tasks. For this purpose, 16 elderly (72 ± 5 years) and 16 young adults (27 ± 5 years) were asked to mentally simulate a static and a dynamic balance task by motor imagery (MI), action observation (AO), or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…As observed during nonpostural motor tasks, (Heuninckx et al 2005(Heuninckx et al , 2008, older adults exhibit increased activity in somatosensory cortices (right postcentral gyrus) during motor imagery of upright stance compared with young adults (Zwergal et al 2012). Similarly, Mouthon et al (2018) reported a greater activity in the supplementary motor area, motor area, premotor cortex, and putamen of older adults during motor imagery of upright standing in various conditions compared with young adults. This engagement of additional cortical areas most likely reflects a compensatory mechanism for age-related sensorimotor decline (Heuninckx et al 2008; Reuter-Lorenz and Lustig 2005).…”
Section: Signal Integrationmentioning
confidence: 80%
“…As observed during nonpostural motor tasks, (Heuninckx et al 2005(Heuninckx et al , 2008, older adults exhibit increased activity in somatosensory cortices (right postcentral gyrus) during motor imagery of upright stance compared with young adults (Zwergal et al 2012). Similarly, Mouthon et al (2018) reported a greater activity in the supplementary motor area, motor area, premotor cortex, and putamen of older adults during motor imagery of upright standing in various conditions compared with young adults. This engagement of additional cortical areas most likely reflects a compensatory mechanism for age-related sensorimotor decline (Heuninckx et al 2008; Reuter-Lorenz and Lustig 2005).…”
Section: Signal Integrationmentioning
confidence: 80%
“…Effects were found in areas including multisensory vestibular cortices and somatosensory cortices during MI of upright standing (Zwergal et al, 2012 ) as well as in the SMA and frontal cortices for MI of gait (Allali et al, 2014 ). Most notably, using MI, AO, and the combination of the two (AO+MI) of balance tasks, we recently found over-activations in the same older adults who participated in the present study in SMA, primary motor cortex (M1), PMC, putamen and PFC (Mouthon et al, in press ). In line with these imaging studies, electrophysiological measurements using transcranial magnetic stimulation (TMS) revealed that motor simulation of balance tasks was associated with greater corticospinal excitability in older compared to young adults (Mouthon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 57%
“…Using motor imagery (MI) and action observation (AO), also standing and walking have been investigated with fMRI and similar effects of greater brain activity in older relative to young adults have been reported (Zwergal et al, 2012 ; Allali et al, 2014 ; Mouthon et al, in press ). Effects were found in areas including multisensory vestibular cortices and somatosensory cortices during MI of upright standing (Zwergal et al, 2012 ) as well as in the SMA and frontal cortices for MI of gait (Allali et al, 2014 ).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the systematic observation of significant motor actions closely linked to their execution (action observation treatment (AOT)) has been proposed to be a valuable and feasible practice for motor-impaired patients [ 2 ]. As reported by Abruzzese and colleagues, Action Observation (AO) therapy shows its effectiveness in learning or enhancing the quality of execution of specific motor skills [ 3 ], and it has been described as an effective cognitive tool for rehabilitation [ 2 , 4 , 5 , 6 ], since it can shape neural circuit reorganization and promote neural plasticity and motor learning [ 7 , 8 , 9 , 10 , 11 ]. Despite this promising evidence, very few studies have been published about the rehabilitation of People with Parkinson’s (PwP) using the AO paradigm [ 3 ].…”
mentioning
confidence: 99%